Reception Analysis Masyarakat Surabaya terhadap Wacana Presiden 3 Periode - Rizal Wahyu Saputra; Dyva Claretta Claretta (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This research is motivated by the 3-period presidential discourse in the Indonesia Lawyers Club (ILC) program. This study aims to determine public acceptance of the 3-term presidential discourse on the YouTube channel Indonesia Lawyers Club (ILC) episode "Harga-Harga Naik, Tapi Publik Puas Terhadap Jokowi". The research method uses a qualitative reception analysis approach with the encoding-decoding model by Stuart Hall to understand community reception. Stuart Hall divides the categories of audience acceptance into 3 positions, namely dominant, negotiated, and oppositional. Data collection techniques were carried out by in-depth interviews. The results of the study show that the public does not agree with the existence of a 3-term president, because this is contrary to the constitution and the basis of the 1945 Constitution that applies in Indonesia. Even though all informants acknowledged Pak Jokowi's performance, according to the informants, Pak Jokowi was not fit to continue his term of office because doing so could undermine reforms and damage the state order. Keywords: Reception analysis, 3 period presidential discourse, Indonesia Lawyers Club